A prototype of pCT scanner: first tests - Briz J. A. (EDP Sciences, 2021)
Proton therapy technique for cancer treatment offers a high selectivity with respect to conventional radiotherapy with X- and γ-rays due to the properties of the interaction of protons with matter. Very accurate and precise treatment plans and a good control on the dose deposition are required to exploit the full potential of the technique. The substitution of the currently used X-ray Computed Tomography (xCT) by proton Computed Tomography (pCT) in the design of treatment plans would allow for a reduction in proton range uncertainties. This would make possible an important improvement in the accuracy and precision of treatment plans. With this aim, a prototype of pCT scanner is under study. It includes two tracking detectors which provide information on the proton trajectories and a residual energy detector to determine the energy loss while traversing the object scanned. A proof-of-concept experiment has been performed using low-energy protons and a simplified prototype with only the two tracking detectors. The results obtained in the measurement are presented and discussed.